2010
DOI: 10.1016/j.healun.2009.11.317
|View full text |Cite
|
Sign up to set email alerts
|

304: Alemtuzumab Induction Facilitates Steroid-Free Immunosuppression in Human Cardiac Transplantation: Two Year Outcomes

Abstract: Purpose: Lymphocytic bronchiolitis (LB) is the strongest risk factor for subsequent allograft loss due to obliterative bronchiolitis (OB), however it is poorly assessed by transbronchial biopsy (TBBx) because of sampling error, interpretation error, and the presence of non-alloreactive airway inflammation. We hypothesised that flow cytometric interrogation of small airway brushings -the 'B score' may be a better tool. Methods and Materials: 43 small airway brushings (2-3 cm from pleural surface, 2mm OD Olympus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Increases in freedom from rejection in the alemtuzumab group were maintained for up to 5 years (73% vs 56% with controls, P ¼ .0002). [13][14][15][16] Although we did not observe a reduction in grade !2 rejection, this discrepancy can be explained by the inclusion of AMR in our composite end point as prior studies did not either specify or report AMR episodes. [11][12][13] When ACR was analyzed independently, alemtuzumab was associated with lower rates of both grade !2 ACR and any grade of ACR despite lower immunosuppression therapy, a difference that is consistent with prior studies.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Increases in freedom from rejection in the alemtuzumab group were maintained for up to 5 years (73% vs 56% with controls, P ¼ .0002). [13][14][15][16] Although we did not observe a reduction in grade !2 rejection, this discrepancy can be explained by the inclusion of AMR in our composite end point as prior studies did not either specify or report AMR episodes. [11][12][13] When ACR was analyzed independently, alemtuzumab was associated with lower rates of both grade !2 ACR and any grade of ACR despite lower immunosuppression therapy, a difference that is consistent with prior studies.…”
Section: Discussioncontrasting
confidence: 54%
“…Although alemtuzumab induction is fairly common in kidney transplantation, only limited experience in OHT has been described, with follow-up outcomes reported at up to 5 years. [6][7][8][9][10][11][12][13][14][15][16] In these analyses, alemtuzumab reduced the rates of rejection and extended time to rejection but had no impact on survival. Additionally, in the largest study to date, renal function at 12 months was significantly worse among patients who received alemtuzumab, despite lower tacrolimus concentrations (49.8 + 17 vs 55.2 + 15 mL/min with standard immunosuppression, P ¼ .04).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators from the University of Pittsburgh additionally reported 2-, 3-, and 4-year outcomes from their retrospective review. [21][22][23] The same study and control patients reviewed at 1 year were included in the 2year review. 21 Overall survival remained no different between groups (alemtuzumab 86% vs control 90%, P = .30), and alemtuzumab patients continued to have greater freedom from significant rejection (2R or greater) (81% vs 50%, P < .001).…”
Section: Efficacy Resultsmentioning
confidence: 99%
“…One retrospective cohort, 1 case series, 1 case-control series, and 1 open-label trial were identified and are detailed here. [17][18][19][20][21][22]…”
Section: Methodsmentioning
confidence: 99%
“…Early results from a small retrospective study [41] and a small randomized trial [42] were promising, with similar survival, but fewer rejections, in HTs with alemtuzumab vs. HTs without alemtuzumab. These initial results were then confirmed in a larger case control series by Teuteberg et al [43][44][45][46][47]. Further studies on alemtuzumab are, however, needed before its routine use can be considered [48].…”
Section: Anti-cd52 Antibodiesmentioning
confidence: 74%